Volume 1A: Aircraft Engine; Fans and Blowers 2014
DOI: 10.1115/gt2014-26142
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamics of Boundary Layer Ingesting Fans

Abstract: Boundary Layer Ingesting (BLI) turbofan engines could offer reduced fuel burn compared with podded engines, but the fan stage must be designed to run continuously with severe inlet distortion. This paper aims to explain the fluid dynamics and loss sources in BLI fans running at a cruise condition. High-resolution experimental measurements and full-annulus unsteady CFD have been performed on a low-speed fan rig running with a representative BLI inlet velocity profile. A three-dimensional flow redistribution is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
123
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(134 citation statements)
references
References 0 publications
11
123
0
Order By: Relevance
“…Results expressed in the rotor frame of reference revealed that the flow distortion increased the relative incidence angle by up to approximately 10 in the outer annuli of the duct at the fan face plane. A similar test case [31] showed that absolute swirl angles could increase up to 10 in the main coswirling and counter-swirling regions. Prior studies [3][4] have demonstrated that the peak swirl angles at the S-duct outlet are proportional to the duct offset ratio (h/Din).…”
Section: A Time-averaged Flow Fieldmentioning
confidence: 84%
“…Results expressed in the rotor frame of reference revealed that the flow distortion increased the relative incidence angle by up to approximately 10 in the outer annuli of the duct at the fan face plane. A similar test case [31] showed that absolute swirl angles could increase up to 10 in the main coswirling and counter-swirling regions. Prior studies [3][4] have demonstrated that the peak swirl angles at the S-duct outlet are proportional to the duct offset ratio (h/Din).…”
Section: A Time-averaged Flow Fieldmentioning
confidence: 84%
“…While vehicular efficiency quantification (equation (32)) necessitates an instantaneous # at the considered operating point, the evaluation of fuel burn based on the solution of the Breguet-Coffin equation presented in equation (30) requires aircraft gross weight to be determined at the end of ÁR. Hence, equation (32) can be used to solve equation (30) for both aircraft and to analytically express the consumed fuel mass of the PFC aircraft Ám f,PFC for a given range segment ÁR as a function of the determined PSC, the vehicular efficiency of the reference aircraft ov Á L=D ð Þ Ref as well as the aircraft gross weight ratios at the representative operating point and at the end of range segment, # and # end…”
Section: Analytical Formulation Of Power and Fuel Savingsmentioning
confidence: 99%
“…Both rotor and stator are comprised of 15 blades/vanes. The inflow distortion (depicted in Figure 5b) models an ingested boundary layer of an airplane fuselage and is similar to the ones presented by [18,19]. It has the form of an ideal turbulent boundary layer that covers 50% of the inlet duct height in the lower part of the annulus.…”
Section: Fan Simulation With Inlet Distortionmentioning
confidence: 87%
“…Figure 6b,c show a well-known influence mechanism of ingested boundary layers on fan stages: due to reduced inflow velocity in the distorted area, the overall mass flow rate is reduced while the global total pressure ratio rises due to an increased inflow and hence incidence angle [20]. For the same reason, the distorted inflow reduces the isentropic efficiency of the fan stage [18]. The results show that the decrease in mass flow and the increase in total pressure ratio are predicted correctly by the HB simulations as well as by the mixing plane results with inlet distortion.…”
Section: Fan Simulation With Inlet Distortionmentioning
confidence: 99%